Efectos del Brexit sobre el comercio internacional de Reino Unido : ÅAbandonar la Unión Europea significaría un retroceso de la globalización en este país? (2017)
United Kingdom recently decided to leave the European Union (Brexit) and, as a result, the country's international commerce is about to change. In this study, using the gravity model of trade and panel data techniques, it was found the impact of certain variables on the international trade of the United Kingdom (UK) and it was analyzed what would be the effect of Brexit over the most important variable, finding the possible consequences of this event over the UK?s international trade. The results showed that the commercial activity diminishes if the European Union member countries modify their trade agreements with the United Kingdom, which is most likely, leading to a setback of the globalization of this nation and, therefore, affecting its economy.